Urban Ecological Design A Process for Regenerative Places - Palazzo, Danilo; Steiner, Frederick; SpringerLink (Online service) (Washington, DC : Island Press/Center for Resource Economics : Imprint: Island Press, 2012)
Urban Ecological Design presents an interdisciplinary method of transforming urban spaces that considers issues of ecology and sustainability alongside urban form. Rather than offer a prescriptive approach, the authors describe a (3z(Bprocess model(3y (Bthat has been developed and tested over time. They illustrate the different stages of the design process using theories, techniques, images, and case studies that will inform any urban design project.s
List of Illustrations -- Acknowledgments -- Foreword -- Introduction -- 1. Processes -- 2. Prerequisites -- 3. Knowledge -- 4. Synthesis -- 5. Options -- 6. Dialogues -- 7. Master Plan -- 8. Presentation -- 9. Details -- 10. Implementation -- 11. Conclusion -- Bibliography -- Index.
Keywords: Environmental sciences; Architecture; Design and construction; Urban Ecology; Environmental management; Environment; Environmental Management; Urbanism; Cities, Countries, Regions; Design, general; Urban Ecology